Three-Dimensional-Printed Oral Films Based on LCD: Influence Factors of the Film Printability and Received Qualities - Tingfeng Xu; Huijie Li; Yi Xia; Sheng Ding; Qingliang Yang; Gensheng Yang (MDPI AG, 2023)
As an oral mucosal drug delivery system, oral films have been of wide concern in recent years because of their advantages such as rapid absorption, being easy to swallow and avoiding the first-pass effect common for mucoadhesive oral films. However, the currently utilized manufacturing approaches including solvent casting have many limitations, such as solvent residue and difficulties in drying, and are not suitable for personalized customization. To solve these problems, the present study utilizes liquid crystal display (LCD), a photopolymerization-based 3D printing technique, to fabricate mucoadhesive films for oral mucosal drug delivery. The designed printing formulation includes PEGDA as the printing resin, TPO as the photoinitiator, tartrazine as the photoabsorber, PEG 300 as the additive and HPMC as the bioadhesive material. The influence of printing formulation and printing parameters on the printing formability of the oral films were elucidated in depth, and the results suggested that PEG 300 in the formulation not only provided the necessary flexibility of the printed oral films, but also improved drug release rate due to its role as pore former in the produced films. The presence of HPMC could greatly improve the adhesiveness of the 3D-printed oral films, but excessive HPMC increased the viscosity of the printing resin solution, which could strongly hinder the photo-crosslinking reaction and reduce printability. Based on the optimized printing formulation and printing parameters, the bilayer oral films containing a backing layer and an adhesive layer were successfully printed with stable dimensions, adequate mechanical properties, strong adhesion ability, desirable drug release and efficient in vivo therapeutic efficacy. All these results indicated that an LCD-based 3D printing technique is a promising alternative to precisely fabricate oral films for personalized medicine.